Leaf Decoction of Carica papaya Combined with Artesunate Prevents Recrudescence in Plasmodium berghei-Infected Mice - Sannella, Anna Rosa; Karioti, Anastasia; Orsini, Stefania; Scalone, Aldo; Gradoni, Luigi; Messori, Luigi; Severini, Carlo; Bilia, Anna Rita (Planta Medica, 2019)
Malaria treatment and control have become increasingly difficult because of the spread of drug-resistant strains of Plasmodium falciparum and Plasmodium vivax. Thus, there is a continuous need to develop new combination therapies such as artemisinin-based combination therapies (ACTs) to contrast the emergence of resistant Plasmodium strains. Despite ACT has been recommended by the World Health Organization since 2001, its overall deployment in poor endemic areas is very slow, principally due to its high cost. In the malaria endemic areas, plant remedies are still widely used mostly without assurance of their efficacy and/or safety. A variety of widespread herbal drugs or natural products were already reported for their possible plasmodicidal activities, but the studies concerning their activity in combination with artemisinins are very scarce. The antimalarial activity of papaya is mostly anecdotal, and the present study is aimed at investigating the antiplasmodial activity of a decoction obtained by traditional recipe from the mature leaves of Carica papaya. The decoction was analyzed by HPLC-DAD-MS (high performance liquid chromatography coupled with diodoarray detector and mass spectrometry) showing the presence of caffeoyl derivatives and di- and triglycosides of flavonols. The extract was found to be active against P. falciparum 3D7 strains with a synergism in the presence of artemisinin. In vivo activity against the murine malaria model of Plasmodium berghei was disclosed both for the dried extract alone (250, 500, and 750 mg/kg/d) and for its combination with artesunate (250 mg/kg/d papaya plus 10 mg/kg/d artesunate). This combination displayed the greatest antimalarial activity in terms of reduction of parasitemia and prevention of recrudescence in animals recovered from the infection.
Keywords: Carica papaya; Caricaceae; traditional mature leaf decoction; artemisinin and artesunate; in vitro synergistic effect; in vivo activity and recrudescence control